Receptor activator for nuclear factor κ B expression predicts poor prognosis in breast cancer patients with bone metastasis but not in patients with visceral metastasis. Issue 1 (2nd November 2011) - Zhang, Lingyun; Teng, Yuee; Zhang, Ye; Liu, Jing; Xu, Ling; Qu, Jinglei; Hou, Kezuo; Yang, Xianghong; Liu, Yunpeng; Qu, Xiujuan
Abstract : Background: It was recently reported that receptor activator for nuclear factor κ B ligand (RANKL)/receptor activator for nuclear factor κ B (RANK) pathway is critical for RANK-expressing cancer cells to home to bone and associates with disease progression of cancer. The present study was aimed to evaluate the effect of RANK on prognosis in breast cancer patients with bone metastasis and patients with visceral metastasis. Methods: Immunohistochemical staining for RANK was carried out on paraffin-embedded primary tumour tissue sections from 102 patients with metastatic breast cancer. Survival analysis and Cox proportional hazards model were used to explore the prognostic value of RANK expression in breast cancer. Results: The RANK expression rates were 47.1% in metastatic breast cancer. Patients with RANK expression showed significantly poor progression-free survival and disease-specific survival. Subgroup analysis demonstrated that the significant difference in prognosis completely resulted from the occurrence of bone metastasis. Multivariate analysis demonstrated that RANK expression was an independent predictor of bone metastasis-free survival and disease-specific survival in patients with bone metastasis. Conclusions: RANK expression might be an independent predictor of poor prognosis in breast cancer patients with bone metastasis, and RANK expression does not associate with the prognosis in patients with visceral metastasis.